2007
DOI: 10.1111/j.1538-7836.2006.02258.x
|View full text |Cite
|
Sign up to set email alerts
|

An online database of mutations and polymorphisms in and around the coagulation factor V gene

Abstract: using the Biomerieux (100%) and the IL (89%) methods, but it was rather poor (14%) for the groups using the Biopool and the Dade Behring methods. Results from the second exercise obtained from an equivalent number of participants and the same methods did not show significant variation (not shown).In conclusion, two consecutive surveys involving large numbers of participants and methods confirm results and conclusions stemming from previous surveys [2,3] of a rather wide variability of D-dimer results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Inheritance is usually autosomal recessive with an estimated incidence of one in 1 million [3]. Among rare inherited coagulopathies, FV deficiency is poorly characterized, and only about 50 mutations have been reported so far because of the difficulty in sequencing due to the large size of F5 as well as the low prevalence (http://med.unc.edu/isth/mutations-databases/ FactorV_2007numbers.htm) [8]. In this study, we analyzed five Japanese patients with congenital FV deficiency and identified four novel mutations in F5.…”
Section: Introductionmentioning
confidence: 99%
“…Inheritance is usually autosomal recessive with an estimated incidence of one in 1 million [3]. Among rare inherited coagulopathies, FV deficiency is poorly characterized, and only about 50 mutations have been reported so far because of the difficulty in sequencing due to the large size of F5 as well as the low prevalence (http://med.unc.edu/isth/mutations-databases/ FactorV_2007numbers.htm) [8]. In this study, we analyzed five Japanese patients with congenital FV deficiency and identified four novel mutations in F5.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, platelet FV is stored in a partially activated form that, after exposure on the platelet surface, is further activated by FXa or thrombin and is resistant to APC-catalyzed inactivation. [14][15][16] Congenital FV deficiency (Owren parahemophilia), 17,18 caused by loss-of-function mutations in the F5 gene, 19,20 is a rare (1:10 6 [1 person per million]) bleeding disorder inherited as an autosomal recessive trait. Homozygous and compound heterozygous persons have FV levels lower than 10% and present with a lifelong hemorrhagic diathesis whose severity is poorly correlated with the plasma FV level.…”
Section: Introductionmentioning
confidence: 99%
“…Several deficiency-causing mutations (n ¼ 65) and polymorphisms (n ¼ 700) have been described in the FV gene so far, involving patients with a hemorrhagic diathesis or pseudohomozygotes for APC resistance (i.e., heterozygous carriers of factor V Leiden who also carry factor V deficiency). Most of these mutations modify the sequence of factor V [15][16][17][18][19][20][21][22]. As reviewed by Vos [15], protein-truncating nonsense and frameshift mutations are fairly homogeneously distributed, whereas missense mutations are mostly located in the A2 and C2 domains and virtually lacking from the B domain.…”
Section: Inherited Factor V Deficiencymentioning
confidence: 99%